1991
DOI: 10.1007/bf00179279
|View full text |Cite
|
Sign up to set email alerts
|

Steady-state countercurrent flow in one dimension

Abstract: Two phase countercurrent steady-state flow through permeable media in one dimension is discussed. For steady-state countercurrent flow in water wet porous media, a saturation profile is predicted with the water saturation decreasing in the direction that the water phase is flowing. The de la Cruz and Spanos equations predict that the Muskat relative permeability curves for countercurrent flow will be less than the Muskat relative permeability curves for steady-state cocurrent flow. This result has immediate im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…While this effect is in principle present for any flow situation (Zhang et al 2008), its magnitude varies from situation to situation. It is found to be most significant in countercurrent flow (Eastwood and Spanos 1991). -Relative permeabilities were introduced as parameters for scaling saturated permeability such that 0 ≤ k r α ≤ 1.…”
Section: Known Limitations Of the Two-phase Darcy Approachmentioning
confidence: 99%
“…While this effect is in principle present for any flow situation (Zhang et al 2008), its magnitude varies from situation to situation. It is found to be most significant in countercurrent flow (Eastwood and Spanos 1991). -Relative permeabilities were introduced as parameters for scaling saturated permeability such that 0 ≤ k r α ≤ 1.…”
Section: Known Limitations Of the Two-phase Darcy Approachmentioning
confidence: 99%
“…This reduction was attributed to the differences in the viscous coupling between the two flow settings. Eastwood and Spanos (1991) conducted two-phase flow experiments based on previous modeling done by de la Cruz and Spanos (1983), and their experiments revealed that relative permeability in countercurrent flow settings is less than in cocurrent flow settings. They concluded that relative permeabilities for oil in counter-current flow is always less than for cocurrent flow setting.…”
Section: Relative Permeability and Counter-current Flowmentioning
confidence: 99%
“…They attributed this reduction of relative permeabilities in countercurrent flow to viscous coupling that acts differently in co-current and counter-current flow settings. Eastwood and Spanos (1991) studied two-phase flow in porous media and found that the relative permeability in counter-current flow is less than the relative permeability in co-current flow. Based on the two-phase flow model of de la Cruz and Spanos (1983), they derived that the Muskat relative permeabilities for oil in counter-current flow settings are less than those for co-current flow settings.…”
Section: Introductionmentioning
confidence: 98%